Variant genotypes associated with reduced expression of RhCE antigens among Brazilian blood donors. Issue 6 (9th March 2021) - Dezan, Marcia Regina; Oliveira, Valéria B.; Conrado, Marina C. A. V.; da Rocha, Mateus Cardoso; Luz, Fabio; Gallucci, Antonio; Pereira, Alexandre C.; Krieger, José E.; Rocha, Vanderson; Mendrone‐Junior, Alfredo; Dinardo, Carla Luana
Abstract: Background: The genetic diversity of the RHCE gene locus has been explored in diverse populations of different racial backgrounds. Data referring to the diversity of RHCE encoding weakened expression of C, c, E, and e in multiethnic populations is still incomplete. Methods: Samples from Brazilian blood donors presenting reduced expression of C, c, E, or e on gel method were selected for the study. All exons and flanking introns of RHCE were genotyped though direct Sanger sequencing for the included donors. Results: Sixty‐six donors were included: 23 with weak C, 22 with weak c, 6 with weak E, 14 with weak e, and 1 with weak c and E. Among the samples with weak C, the following altered RH*C were encountered: RHCE*CeMA (n = 3), RHCE*Ce941C (n = 1), and RHCE*CeVA (n = 1). RHD*D‐CE(4–7)‐D was detected in six cases, RHCE*CE was presumably present in five cases, and seven cases were unexplained. Two altered alleles underlay the weak c phenotype: RHCE*ceJAL (n = 20) and RHCE*ce340T (n = 2), and two altered RHCE justified weak e: RHCE*ceMO (n = 6) and RHCE*ceJAL (n = 8). Three variant RHCE were associated with weak E: RHCE*cEJU (n = 4), RHCE*cE382C (n = 1), and RHCE*cEIV (n = 1). The RHCE*cE905A justified one case of weak c and E. Conclusion: We describe the distribution of RHCE variants found in association with weak expression of C, c, E, and e in blood donors of multiethnic origin, which differs in comparison to that previously reported for people of African or Caucasian descent.